2016
DOI: 10.1002/14651858.cd003860.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated radiation therapy for early breast cancer

Abstract: We found that using altered fraction size regimens (greater than 2 Gy per fraction) does not have a clinically meaningful effect on local recurrence, is associated with decreased acute toxicity and does not seem to affect breast appearance, late toxicity or patient-reported quality-of-life measures for selected women treated with breast conserving therapy. These are mostly women with node negative tumours smaller than 3 cm and negative pathological margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 96 publications
4
49
0
3
Order By: Relevance
“…At the time of conception of the IMRT-MC2-trial, normofractionated radiotherapy was the standard of care after breast-conserving surgery for breast cancer. During the conduct of the trial, hypofractionated radiotherapy was shown to be equally effective in terms of tumor control with a slightly lower risk of acute and chronic cutaneous and subcutaneous side effects [ 35 ], a reduction in treatment time and better health economics [ 36 ]. However, for several subgroups, normofractionated radiotherapy is still regarded as the standard of care, especially patients who are planned to receive regional nodal irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of conception of the IMRT-MC2-trial, normofractionated radiotherapy was the standard of care after breast-conserving surgery for breast cancer. During the conduct of the trial, hypofractionated radiotherapy was shown to be equally effective in terms of tumor control with a slightly lower risk of acute and chronic cutaneous and subcutaneous side effects [ 35 ], a reduction in treatment time and better health economics [ 36 ]. However, for several subgroups, normofractionated radiotherapy is still regarded as the standard of care, especially patients who are planned to receive regional nodal irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrate that accelerated partial breast irradiation (APBI) provides, in shorter time, similar rates of local control and similar breast cancer-specific and overall survival outcomes as treatment with whole breast radiation therapy (WBRT) in early-stage breast cancer patients[510]. However, a number of systematic reviews reported a lack of evidence about short-term RT side effects and their impact on changes in quality of life (QOL) [1114]. One review of randomized clinical trials comparing PBI/APBI and conventional or hypo-fractionated WBRT found that no studies reported on the relative effects of PBI/APBI and WBRT on quality of life [15].…”
Section: Introductionmentioning
confidence: 99%
“…Отдельные крупные рандомизированные исследования показывают сопоставимые результаты относительно локального контроля и поздних лучевых повреждений, при достоверном снижении острой лучевой токсичности [10]. Но существуют работы, показавшие преимущество использования методики гипоф-ракционирования в отношении поздних лучевых повреждений и качества жизни [20,21].…”
Section: результатыunclassified
“…При подробном изучении методик гипофракционирования в сравнении с традиционным режимом исследователями были показаны сопоставимые результаты общей и безрецидивной выживаемости [6][7][8]. Также режим гипофракционирования не уступает конвенциональному режиму облучения по безопасности, качеству жизни и косметическим результатам при различных объёмах хирургического лечения, а, по данным некоторых исследований, является методом выбора [9][10]…”
unclassified